2017
DOI: 10.1007/s10815-017-1085-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythrocyte-sperm separation medium on nuclear, acrosomal, and membrane maturity parameters in human sperm

Abstract: ESSM can enhance the efficiency of sperm retrieval protocol and can also decrease the time required to collect spermatozoa while not affecting sperm morphogenetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
0
8
2
Order By: Relevance
“…Although there has been no study with accepted protocols on the effect of ELB on either sperm parameters or DNA fragmentation, Soygur and associates found that ELB treatment in ejaculated spermatozoa had no detrimental effects on sperm parameters and DNA fragmentation. The exposure time in their study was set at only 5–10 s (Soygur et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there has been no study with accepted protocols on the effect of ELB on either sperm parameters or DNA fragmentation, Soygur and associates found that ELB treatment in ejaculated spermatozoa had no detrimental effects on sperm parameters and DNA fragmentation. The exposure time in their study was set at only 5–10 s (Soygur et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The slides were examined by × 1,000 magnification with a light microscope and counting 200 spermatozoa. Unstained or pale blue‐stained cells were considered as normal, and dark blue cells deemed to be abnormal spermatozoa (Soygur et al., 2018). The percentage of abnormal spermatozoa was reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several protocols have been implemented to optimize semen sampling, especially by removing RBC prior to freezing. Such protocols may be based on the application of density gradient centrifugation, erythrocyte-sperm separation media, and microfluidic systems [58][59][60]. The efficacy of gradient centrifugation was confirmed by the successful separation of viable motile canine spermatozoa from dead immotile spermatozoa and RBC using four different types of density gradient centrifugation media [58].…”
Section: Freezability Of Epididymal Semenmentioning
confidence: 97%
“…In addition, osmotic stress caused by the chemical structure of this buffer may damage the plasma membrane and alter sperm metabolism [ 21 ]. Conversely, Soygur et al showed that ELB itself and the cellular stress caused by erythrocyte lysis did not have detrimental effects on the survival of ejaculated sperm [ 22 ]. According to their protocol, however, ELB incubation was only allowed for 5–10 s, so there may not have been enough time for damage to occur.…”
Section: Processing and Selection Of Surgically Retrieved Sperm For Icsimentioning
confidence: 99%